GPU-accelerated adaptive image denoising - Sushchyk, Konstantin (Видавництво Львівської політехніки, 2012)
In this paper an efficient GPU-based implementation of adaptive bilateral filtration is considered.
Keywords: adaptive noise removal; bilateral filtration; GPGPU; CUDA